URBAN INFRASTRUCTURE PROJECTS AND CHALLENGES, RISK IDENTIFYING FOR EMERGING NEW CITIES OF NEPAL - Koirala, Madhav Prasad (International Journal of Research -GRANTHAALAYAH, 2018)
Nepal is beautiful country. According to new geographical structure there are six metropolitan cities, eleven sub-metropolitan cities. Seventeen cities are already urbanized and two hundred and seventy-six municipalities are also newly emerging cities. The objective of this research is mainly urban infrastructure development, its challenges, explore the problems, identify defective coordination within the interdisciplinary ministry, suggest for integrated infrastructure, to aware risk factors associated during urban infrastructures. The methodology adopted was according to various literature reviews and surveys conducted on the sport. Respondent were selected from concerned authorities, this research shows everyone want affordable housing, public hospital, school, college, university, drinking water, communication, drain and sanitation facilities and wide road are prime needs. It was found the defective procurement policy including various risk factors, a lack of adequate government’s act with necessary policies, vision of leader is not globally thinking and locally acting, human resource is not compatible, the poor performance of contactor and consultant, project manager is not being professional and allocating budget is not enough, since one authority built, immediately other authority dig the trench. if government started integrated urban infrastructure projects would better for future and proper risk management plan needs to establish.